Analisis Literasi Keuangan dan Perilaku Keuangan terhadap Pengelolaan Keuangan Pribadi dan Uji Beda Antar Semester pada Mahasiswa Akuntansi FEB UNTAN - Lutfi Amin; Rudy Kurniawan; Ira Grania Mustika (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of financial literacy and financial behavior on personal financial management and to examine the differences in financial literacy, financial behavior, and personal financial management among accounting students across semesters at the Faculty of Economics and Business, Universitas Tanjungpura. This research employed a quantitative approach using descriptive and verificative methods. Data were collected through questionnaires distributed to 118 respondents consisting of 30 second-semester students, 34 fourth-semester students, and 54 sixth-semester students. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and the Kruskal-Wallis test with the assistance of IBM SPSS Statistics 27. The results showed that financial literacy and financial behavior have a positive and significant effect on students’ personal financial management. Furthermore, the Kruskal-Wallis test indicated that there were no significant differences in the levels of financial literacy, financial behavior, and personal financial management among second-, fourth-, and sixth-semester students.